„Gdy wspomnę, w onej szczęsnej dobie czym byłam, a czym dziś się stałam”. Antropologiczno-historyczna analiza motywu młodości i starości w poezji Françoisa Villona - Kulesza, Kamila (Starość i młodość w literaturze i kulturze, 2016)
The main aim of this paper is to analyse the medieval image of young and old age as presented insome poems of François Villon. The analysis, based on the heremeneutic reading of Villon’s poems andinspired by works of the scholars of Annales tradition, focuses on the question of social worth of individualsas determined by their age, with the special reference to the fate of medieval women, condemnedby culture to inevitable loneliness.